Technical Limits of Passivity-Based Control Gains for a Single-Phase Voltage Source Inverter - Zbigniew Rymarski; Krzysztof Bernacki (Energies, 2021)
Passivity-based control (PBC) seems to be predicted for the control algorithms in the voltage source inverters (VSI) for voltage backup systems. This paper presents limitations of the improved (IPBC) version of the PBC (directly measuring the output voltage) maximum voltage and current gains. In a microprocessor-controlled inverter, these depend on the PWM modulator dynamic properties, the switching frequency, the modulation index value (avoiding modulator saturation and enabling the rapid increase of the filter inductor current), and the parameters of the VSI output filter. A single switching period delay of the digital PWM modulator was considered in the theoretical calculations based on a discrete inverter model. The simulations for the standard nonlinear rectifier RC load enabled the initial adjustment of the IPBC border gains, which depended on the switching frequency. Some small harmonics oscillations of the output voltage were acceptable for the test rectifier RC load or dynamic load. However, oscillations of the inductor current increased the power losses in the coil core. Experimental verification of the simulation results using a laboratory VSI model is also presented.